Measurement of the spin density matrix for the rho(0), K*(0)(892) and phi produced in Z(0) decays - Abreu, P; Adam, W; Adye, T; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andersson, P; Andreazza, A; Antilogus, P; et al. (1997)
The spin density matrix elements for the ρ0, K*0(892) and φ produced in hadronic Z0 decays are measured in the DELPHI detector. There is no evidence for spin alignment of the K*0(892) and φ in the region xp ≤ 0.3 (xp = p/pbeam), where ρ00 = 0.33 ± 0.05 and ρ00 = 0.30 ± 0.04, respectively. In the fragmentation region, xp ≥ 0.4, there is some indication for spin alignment of the ρ0 and K*0(892), since ρ00 = 0.43 ± 0.05 and ρ00 = 0.46 ± 0.08, respectively. These values are compared with those found in meson-induced hadronic reactions. For the φ, ρ00 = 0.30 ± 0.04 for xp ≥ 0.4 and 0.55 ± 0.10 for xp ≥ 0.7. The off-diagonal spin density matrix element ρ1 - 1 is consistent with zero in all cases.© 1997 Published by Elsevier Science B.V.